Analisis Rasio Profitabilitas Dan Solvabilitas Dalam Mengukur Kinerja Keuangan Pada PT. Astra Internasional Tbk - Jessica Nadaa Vallentiantara; Ifa Nurmasari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the financial performance of PT. Astra Internasional Tbk using Profitability and Solvency ratios. This research was analyzed using quantitative descriptive analysis techniques, namely data in the form of numbers which include financial reports in the form of balance sheets and profit and loss data reports at PT. Astra Internasional Tbk from 2014 to 2023 which describes real conditions or events at the company. This research uses Profitability ratio analysis using return on assets (ROA) and return on equity (ROE) calculations and Solvency ratios using debt to assets ratio (DAR) and debt to equity ratio (DER) calculations. The results of the research show that the financial performance of PT Astra Internasional in terms of Profitability Ratios is above the average of similar companies with a return on assets value of 7,8% compared to 6,9%, a return on equity value of 14,0% compared to 11,0% and a Ratio Solvency is below the average of similar companies with a debt to asset ratio of 45,6% compared to 47,0%, a debt to equity ratio of 84,4% compared to 127,7%. This is because the company is quite capable of optimizing the resources owned by the company. Both from resources in the form of capital, assets and investments that are sufficient to produce a profit or profit in terms of their use.